National trends in thyroid disease and COVID-19 pandemic-related factors, 1998–2021: A nationwide representative study in South Korea - Kyeongmin Lee; Jaeyu Park; Myeongcheol Lee; Hojae Lee; Yejun Son; Hyejun Kim; Jiseung Kang; Yujin Choi; Sang Youl Rhee; Masoud Rahmati; Ai Koyanagi; Lee Smith; et al. (Heliyon)
Objective: Although thyroid disease is a common condition, there is limited research examining the prevalence of thyroid disease over a long period of time, including both before and during the COVID-19 pandemic. Therefore, we aimed to investigate sociodemographic aspects that might be associated with thyroid disease and how its prevalence has varied during the pandemic. Methods: We assessed the prevalence of thyroid disease among Korean adults by using data from the Korea National Health and Nutrition Examination Survey from 1998 to 2021. We evaluated weighted prevalence and β-coefficients with 95 % CI for factors such as age, sex, residential area, education level, household income, perceived stress level, weight change, occupation category, and body mass index groups. Results: From 1998 to 2021, the prevalence of thyroid disease among 159,896 Korean adults (88,120 females [55.1 %]) aged 20 years and older exhibited an overall increasing trend. The weighted prevalence in the general population rose from 1.52 % (95 % CI, 1.41–1.64) in 1998–2005 to 3.84 % (3.30–4.39) in 2021, with a higher likelihood of thyroid disease exposure as age increased. In addition, females, individuals with lower education levels, those with high levels of perceived stress, those who gained weight, and those classified as overweight or obese emerged as vulnerable groups for thyroid disease. For the majority of subgroups, the change amid the effect of the pandemic on prevalence was minimal. However, the aged ≥60 years group showed a greater increase in prevalence during the pandemic than before the pandemic (βdiff: 0.52 [95 % CI, 0.37–0.68]). Conclusions: A nationwide representative study in South Korea revealed an increasing trend in the prevalence of thyroid disease over 24 years, particularly among the older population. Despite the minimal variation during the pandemic, our findings emphasize the need for targeted thyroid disease policies and further research, especially for specific subgroups such as the older population.